Garra dengba, a new species of cyprinid fish (Pisces: Teleostei) from eastern Tibet, China - Deng, Shu-Qing; Cao, Liang; Zhang, E (Zootaxa, 2018)
Garra dengba is here described from the Chayu-Qu, a tributary flowing into the Brahmaputra River, in Chayu County, eastern Tibet, China. It shares the presence of an incipient proboscis on the snout with G. arupi, G. elongata, G. gravelyi, G. kalpangi, and G. rotundinasus, but is distinguished from these five species in having, among other features, fewer branched dorsal- and anal-fin rays and more perforated lateral-line scales. Its validity was also confirmed by a molecular phylogenetic analysis based on the cytochrome b gene.